2024
DOI: 10.1002/ps.8071
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in IAA16 is associated with dicamba resistance in Chenopodium album

Hossein Ghanizadeh,
Lulu He,
Andrew G. Griffiths
et al.

Abstract: BACKGROUNDResistance to dicamba in Chenopodium album was first documented over a decade ago, however, the molecular basis of dicamba resistance in this species has not been elucidated. In this research, the resistance mechanism in a dicamba‐resistant C. album phenotype was investigated using a transcriptomics (RNA‐Seq) approach.RESULTSThe dose–response assay showed that the resistant phenotype (R) was nearly 25‐fold more resistant to dicamba than a susceptible phenotype (S) of C. album. Also, dicamba treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…LeClere et al (2018) showed that a substitution of this glycine to asparagine in BsAUX/IAA16 is sufficient for dicamba resistance in kochia. Similarly, Ghanizadeh et al (2024) associate a substitution of this glycine to aspartic acid with dicamba resistance in Chenopodium album, a closely related species. Finally, NMR experiments by Ramans-Harborough et al (2023) show that this glycine is involved in the interaction between IAA and TIR1.…”
Section: A Transposable Element Insertion In Bsiaa16 Causes a Change ...mentioning
confidence: 95%
See 2 more Smart Citations
“…LeClere et al (2018) showed that a substitution of this glycine to asparagine in BsAUX/IAA16 is sufficient for dicamba resistance in kochia. Similarly, Ghanizadeh et al (2024) associate a substitution of this glycine to aspartic acid with dicamba resistance in Chenopodium album, a closely related species. Finally, NMR experiments by Ramans-Harborough et al (2023) show that this glycine is involved in the interaction between IAA and TIR1.…”
Section: A Transposable Element Insertion In Bsiaa16 Causes a Change ...mentioning
confidence: 95%
“…A genome scan associating this genotype information to visual injury rating identified one significant QTL that peaks at 88 Mbp on chromosome 4 (Figure 2A). This interval contains BsAUX/IAA16 at 87.4 Mbp, a gene that is important for the signaling of auxin and has been implicated in auxin herbicide resistance in kochia and a closely related species (LeClere et al, 2018;Ghanizadeh et al, 2024). The genotype of BsAUX/IAA16 within this QTL of plants from an independent segregating F3 line explained 43% of variation in visual injury following dicamba treatment at 560 g ha -1 (Figure 2B).…”
Section: A Single Locus On Chromosome 4 Is Associated With Dicamba Re...mentioning
confidence: 99%
See 1 more Smart Citation